2018
DOI: 10.1111/famp.12382
|View full text |Cite
|
Sign up to set email alerts
|

The Relational Mind in Couple Therapy: A Bateson‐Inspired View of Human Life as an Embodied Stream

Abstract: Research on human intersubjectivity has found that humans participate in a dialogue throughout their life, and that this is manifested not only via language, but also nonverbally, with the entire body. Such an understanding of human life has brought into focus some basic systemic ideas concerning the human relational mind. For Gregory Bateson, the mind works as a system, formed from components that are in continuous interaction with each other. In our Relational Mind research project, we followed twelve couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
(52 reference statements)
0
22
0
3
Order By: Relevance
“…Palumbo et al ., ; Timmons, Margolin & Saxbe, ). There are only a handful of studies examining participants’ physiological linkage in actual therapy sessions; in these, physiological linkage has been shown to be associated with ratings of empathy and rapport, to play a role in subject positioning, and to occur at significant moments in the session (Karvonen et al ., ; Marci et al ., ; Seikkula et al ., , ). This literature is still in its infancy, is characterized by methodological and conceptual diversity, and our knowledge of the ways in which autonomic arousal is implicated with affect regulation and mutual co‐regulation in therapy is limited.…”
Section: Relational Processes Of Meaning‐makingmentioning
confidence: 99%
“…Palumbo et al ., ; Timmons, Margolin & Saxbe, ). There are only a handful of studies examining participants’ physiological linkage in actual therapy sessions; in these, physiological linkage has been shown to be associated with ratings of empathy and rapport, to play a role in subject positioning, and to occur at significant moments in the session (Karvonen et al ., ; Marci et al ., ; Seikkula et al ., , ). This literature is still in its infancy, is characterized by methodological and conceptual diversity, and our knowledge of the ways in which autonomic arousal is implicated with affect regulation and mutual co‐regulation in therapy is limited.…”
Section: Relational Processes Of Meaning‐makingmentioning
confidence: 99%
“…Another group of recent studies examining autonomic arousal in psychotherapy focus on physiological concordance or linkage, 'the social coupling of two (or more) individuals in the hereand-now of a communication context that emerges alongside, and in addition to, their verbal exchanges' (Tschacher and Meier, 2020, p. 558). Some early studies showed evidence for autonomic concordance between clients and therapists (e.g., DiMascio et al, 1957), a finding that has been explored further more recently (e.g., Marci et al, 2007;Villmann et al, 2008;Karvonen et al, 2015;Seikkula et al, 2015Seikkula et al, , 2018Kodama et al, 2018;Tschacher and Meier, 2020). Findings from these studies are mixed; however, one finding that has been shown across several studies on psychotherapy sessions (as well as in studies of simulated sessions, e.g., Marci and Orr, 2006;Messina et al, 2013;Palmieri et al, 2018) is a correlation between ratings of empathy and the degree of physiological linkage between therapist and client.…”
Section: Interpersonal Physiology and Psychotherapy Processmentioning
confidence: 99%
“…Cada uno de estos términos subraya algún aspecto importante de estos abordajes ya que éstos ven la terapia como un proceso conversacional o discursivo. Las palabras que utilizamos no «reflejan» lo que pensamos o sentimos, sino que le dan forma en gran medida a nuestras ideas y al significado de nuestras experiencias (Anderson y Goolishian, 1988;Seikkula, Karvonen, Kykyri, Penttonen y Nyman-Salonen, 2018).…”
Section: Introductionunclassified